Ideology and power in the Viking and Middle Ages : Scandinavia, Iceland, Ireland, Orkney, and the Faeroes - Steinsland, Gro (Northern world, 2011)
"This book analyses the Nordic pre-Christian ideology of rulership, and its confrontation with, survival into and adaptation to the European Christian ideals during the transition from the Viking to the Middle Ages from the ninth to the thirteenth century"--Provided by publisher.